A new Amazonian Cryptocellus Westwood (Arachnida, Ricinulei) - Tourinho, Ana Lúcia; de Azevedo, Clarissa Salette (Zootaxa, 2007)
Cryptocellus icamiabas sp. nov. is described from an adult male from Amazonas state, Brazil. The new species is a member of the Amazonian foedus group, and is closest to Cryptocellus abaporu Bonaldo & Pinto-da-Rocha, 2003, Cryptocellus becki Platnick, 1977, and Cryptocellus simonis Hansen & Sorensen, 1904. The distribution pattern and morphology of the foedus group are briefly discussed.